2004
DOI: 10.1523/jneurosci.5626-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modular Premotor Drives and Unit Bursts as Primitives for Frog Motor Behaviors

Abstract: Spinal cord modularity impacts on our understanding of reflexes, development, descending systems in normal motor control, and recovery from injury. We used independent component analysis and best-basis or matching pursuit wavepacket analysis to extract the composition and temporal structure of bursts in hindlimb muscles of frogs. These techniques make minimal a priori assumptions about drive and motor pattern structure. We compared premotor drive and burst structures in spinal frogs with less reduced frogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
188
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(201 citation statements)
references
References 67 publications
(82 reference statements)
13
188
0
Order By: Relevance
“…By systematic and quantitative analyses of EMGs from a large number of muscles, we have established the sufficiency of a small number of synergies to describe both the intact and deafferented data sets well. Thus, our results support the hypothesis that the CNS simplifies the daunting task of deriving appropriate muscle patterns for many behaviors by flexible combination of a small number of synergies (Tresch et al, 1999;Hart and Giszter, 2004;Ting and Macpherson, 2005). Our findings also validate our means of identifying the synergies: the NMF algorithm would have failed to uncover any shared synergies if there had been a gross mismatch between the assumptions of the algorithm (such as linearity) and our conceptual model of synergy combination.…”
Section: Muscle Synergies As Centrally Organized Modulessupporting
confidence: 79%
See 1 more Smart Citation
“…By systematic and quantitative analyses of EMGs from a large number of muscles, we have established the sufficiency of a small number of synergies to describe both the intact and deafferented data sets well. Thus, our results support the hypothesis that the CNS simplifies the daunting task of deriving appropriate muscle patterns for many behaviors by flexible combination of a small number of synergies (Tresch et al, 1999;Hart and Giszter, 2004;Ting and Macpherson, 2005). Our findings also validate our means of identifying the synergies: the NMF algorithm would have failed to uncover any shared synergies if there had been a gross mismatch between the assumptions of the algorithm (such as linearity) and our conceptual model of synergy combination.…”
Section: Muscle Synergies As Centrally Organized Modulessupporting
confidence: 79%
“…Previous experiments have suggested that the CNS may simplify control by activating a small number of modules (Grillner, 1985;Bizzi et al, 1991;Stein and Smith, 1997;Tresch et al, 2002), formulated as muscle synergies, or activation profiles across a set of muscles, the linear combination of which can generate diverse motor patterns (Tresch et al, 2002;Hart and Giszter, 2004;Ting and Macpherson, 2005). Previous studies examining this hypothesis have relied on animals with intact afferents (Saltiel et al, 2001) or have characterized predominantly feedforward, ballistic movements, such as cutaneous reflexes (Tresch et al, 1999) and kicking (d'Avella et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that similar PCs were compared irrespective of the amount of variance explained by those PCs, we first computed the dot product of a given PC in a subject with all the three PCs in other subjects. The largest dot product was then considered (see Tresch et al, 1999;Hart and Giszter, 2004). We found that on average the correlation between PCs was 0.77 (± 0.02 SE) and 0.66 (± 0.01 SE) for the Step-push and Step-pull conditions respectively, confirming their similarity across subjects.…”
Section: Identification Of M-modes: Results Of Pcamentioning
confidence: 58%
“…According to one common proposal, the CNS might produce movement through the flexible combination of ''muscle synergies,'' with each such synergy specifying a particular balance of activation across a set of muscles (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). By reducing the number of controlled variables, such a lowdimensional control strategy would simplify the production of movement.…”
mentioning
confidence: 99%